ELECTRICAL AND MAGNETIC PROPERTIES OF SULFIDES - Pearce C.I.; Pattrick R.A.D.; Vaughan D.J. (My University, 2006)
The metal sulfides exhibit a great diversity of electrical and magnetic properties with both scientifi c interest and practical applications. These properties apply major constraints on models of the electronic structure (or chemical bonding) in sulfides (Vaughan and Rosso 2006, this volume). The pure and doped synthetic equivalents of certain sulfide minerals have actual or potential applications in the electronics industries (optical devices, photovoltaics, photodiodes and magnetic recording devices). Sulfides are also components of many thin film devices and have been extensively investigated as part of the nanotechnology revolution. Certain electrical and magnetic properties of sulfide minerals mean they contribute to geomagnetism and paleomagnetism, and provide the geophysical prospector with exploration tools for metalliferous ore deposits. To the mineral technologist, these same properties provide methods for the separation of the metal-bearing sulfides from associated waste minerals after mining and milling and before extraction of the metal by pyrometallurgical or hydrometallurgical treatment.